Association between anxiety and sleep disorders in students of human medicine of the universidad Ricardo Palma, july-december 2017 - De La Cruz Vargas, Jhony Alberto (2018)
ABSTRACT Introduction: The aims of this study were to assess Sleep disorders (SDs) in a group of university students in Perú and to examine the relationship between SDs and anxiety. Methods: An observational cross-sectional, analitic and observational study was conducted at Ricardo Palma University, Peru, during the academic year 2017. Two questionnaires were face-to-face administered to 132 students after obtaining their written consent: The Beck Anxiety Inventory (BAI), and the Oviedo dream sleep-wake patient questionnaire for DS. Results: The average age found was 24.07 + - 2.14 (20-34). According to marital status, 67.42% were single. The prevalence of insomnia according to ICD10 was 31.8% (95% CI: 7.8-13.4%) more frequent in female students (61.9%) than in men (38.9%); and according to DSM IV it was 3.8% (95% CI: 7.8-13.4%) more frequent in female students (80%) than in men (20%). The prevalence of clinically significant anxiety (moderate and severe) was 9.1%, more frequent in female students (66.6%) than in men (33.3%). A statistically significant association was found between anxiety and insomnia DSM IV with an OR: 7.8 IC95% 1.16-52.26 p: 0.01. Conclusion: The magnitude of insomnia in university students of Ricardo Palma university demonstrate the importance of examining sleep health in this population. The association between anxiety and insomnia is significant, highlighting the importance of detecting and treating anxiety promptly and not just insomnia. Key words: Anxiety; Sleep Initiation and Maintenance Disorders; Students; Universities; Cross-Sectional-Studie; Lifestyle medicine. (source: MeSH NLM) DOI:  10.25176/RFMH.v18.n3.1587